2017
DOI: 10.21580/economica.2017.8.2.2368
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Portofolio Nilai Saham: Studi Komparasi Kinerja Saham Syariah dan Nonsyariah

Abstract: <p class="IAbstrakIsi">The objective of this research is to analyze the comparison of sharia and nonsharia stock performance. The sample is a company listed on the Indonesia Stock Exchange, listing from 2013-2017. The sample consists of nonsharia stock (LQ45) and sharia stock (Jakarta Islamic Index). Sampling method used purposive sampling technique. Data analysis technique used Risk-Adjusted Return Measurement and analyzed by using paired sample T-Test. Based on analysis and discussion, there is no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
0
7
0
3
Order By: Relevance
“…It has also been reported that an investor needs an analytical method of calculating the amount of profit and level of risk from an investment (Hariyanto, 2018), and the dynamic portfolio measurement is considered necessary due to the everchanging stock market conditions (Robiyanto, 2018). Meanwhile, it is possible to generally measure portfolios using a single index, Markowitz, Sharpe, Treynor, and several other methods (Mubarok, Darmawan, and Luailiyah, 2017;Oktaviani and Wijayanto, 2015).…”
Section: Portfoliomentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that an investor needs an analytical method of calculating the amount of profit and level of risk from an investment (Hariyanto, 2018), and the dynamic portfolio measurement is considered necessary due to the everchanging stock market conditions (Robiyanto, 2018). Meanwhile, it is possible to generally measure portfolios using a single index, Markowitz, Sharpe, Treynor, and several other methods (Mubarok, Darmawan, and Luailiyah, 2017;Oktaviani and Wijayanto, 2015).…”
Section: Portfoliomentioning
confidence: 99%
“…The performance is, however, currently measured using different methods such as the Sharpe Index, Sortino Ratio, Jensen Index, Treynor Index, and Omega Ratio. The Sharpe Index has the ability to measure market performance by considering the standard deviation of returns with the risks observed through return on total risk (Mubarok et al, 2017).…”
Section: Portfolio Performance Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This measurement is based on risk adjusted performance with three types of measurement, Sharpe, Treynor and Jensen Index. When compared based on annual data, the performance of the JII portfolio is more resilient to unstable macroeconomic conditions [6].…”
Section: A) Sharpe's Measeurementioning
confidence: 99%
“…principles in which all of these companies' mechanisms and production do not conflict with Islamic law. Jakarta Islamic Index (JII) is one of the Islamic stock indexes in Indonesia (Mubarok, Darmawan, & Luailiyah, 2017). Based on Figure 1, the Islamic stocks are increasing in number from 2013 to 2019.…”
Section: Introductionmentioning
confidence: 99%